2008
DOI: 10.1196/annals.1447.027
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immune Response to Islet Autoantigens in Japanese Patients with Type 1 Diabetes

Abstract: In this study, we evaluated autoantibodies to IA-2 (IA-2As), glutamic acid decarboxylase 65 (GADAs), and islet cell antibodies (ICAs) in 233 patients with type 1 diabetes (M:F = 90:143, mean duration 4.0 +/- 6.7 yr) as a cross-sectional study. Of 233 patients with type 1 diabetes, IA-2A was detected in 58% of patients with duration within 2 weeks, 61% of patients with duration <1 yr, 41% of patients with diabetes for 1-3 yr, 29% for 4-9 yr, and 21% for >or=10 yr. These prevalences were similar to those of ICA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
1
1
Order By: Relevance
“…GAD antibody and islet cell antibody were positive in 85% and 49% of type 1 diabetic patients, respectively (Table 3). The frequency of GAD antibody was relatively higher than that reported in Japanese type 1 diabetic patients (63–74%) 3 . GAD antibody sero‐conversion was observed in 7 patients who had no detectable GAD antibody before starting IFN therapy.…”
Section: Resultscontrasting
confidence: 53%
“…GAD antibody and islet cell antibody were positive in 85% and 49% of type 1 diabetic patients, respectively (Table 3). The frequency of GAD antibody was relatively higher than that reported in Japanese type 1 diabetic patients (63–74%) 3 . GAD antibody sero‐conversion was observed in 7 patients who had no detectable GAD antibody before starting IFN therapy.…”
Section: Resultscontrasting
confidence: 53%
“…Others have reported that slowly progressive type 1 diabetic patients 14,15 or females 7,16 are more likely to be GADA-positive than acute-onset type 1 diabetes or males, respectively. Univariate analysis showed that GADA positivity is more likely in those with slowly progressive type 1 diabetes (OR 2.24, 95% confidence interval 1.14-4.41, P = 0.020), but not females (Table S2).…”
Section: Interaction Of Duration Of Diabetes and Age Of Onset On Antimentioning
confidence: 99%